Two-component system ArcBA modulates cell motility and biofilm formation in Dickeya oryzae - Lv, Mingfa; Ye, Sixuan; Hu, Ming; Xue, Yang; Liang, Zhibin; Zhou, Xiaofan; Zhang, Lianhui; Zhou, Jianuan (Frontiers in Plant Science, 2022)
Phytopathogen Dickeya oryzae is a causal agent of rice foot rot disease and the pathogen has an array of virulence factors, such as phytotoxin zeamines, plant cell wall degrading enzymes, cell motility, and biofilms, collectively contributing to the bacterial pathogenesis. In this study, through deletion analysis of predicted regulatory genes in D. oryzae EC1, we identified a two-component system associated with the regulation of bacterial virulence. The two-component system contains a histidine kinase ArcB and a response regulator ArcA, and deletion of their coding genes resulted in changed phenotypes in cell motility, biofilm formation, and bacterial virulence. Electrophoretic mobility shift assay revealed that ArcA bound to the promoters of the bcs operon and bssS, which respectively encode enzymes for the synthesis of celluloses and a biofilm formation regulatory protein. ArcA could also bind to the promoters of three virulence associated transcriptional regulatory genes, i.e., fis, slyA and ohrR. Surprisingly, although these three regulators were shown to modulate the production of cell wall degrading enzymes and zeamines, deletion of arcB and arcA did not seem to affect these phenotypes. Taken together, the findings from this study unveiled a new two-component system associated with the bacterial pathogenesis, which contributes to the virulence of D. oryzae mainly through its action on bacterial motility and biofilm formation.